“Modulating Phosphoinositide Profiles as a Roadmap for Treatment in Acute Myeloid Leukemia” - Ratti, Stefano; Evangelisti, Camilla; Mongiorgi, Sara; De Stefano, Alessia; Fazio, Antonietta; Bonomini, Francesca; Follo, Matilde Y.; Faenza, Irene; Manzoli, Lucia; Sheth, Bhavwanti; Vidalle, Magdalena C.; Kimber, Scott T.; et al. (Frontiers in Oncology, 2021)
Polyphosphoinositides (PPIns) and their modulating enzymes are involved in regulating many important cellular functions including proliferation, differentiation or gene expression, and their deregulation is involved in human diseases such as metabolic syndromes, neurodegenerative disorders and cancer, including Acute Myeloid Leukemia (AML). Given that PPIns regulating enzymes are highly druggable targets, a number of studies have recently highlighted the potential of targeting them in AML. For instance many inhibitors targeting the PI3K pathway are in various stages of clinical development and more recently other novel enzymes such as PIP4K2A have been implicated as AML targets. PPIns have distinct subcellular organelle profiles, in part driven by the specific localisation of enzymes that metabolise them. In particular, in the nucleus, PPIns are regulated in response to various extracellular and intracellular pathways and interact with specific nuclear proteins to control epigenetic cell state. While AML does not normally manifest with as many mutations as other cancers, it does appear in large part to be a disease of dysregulation of epigenetic signalling and many novel therapeutics are aimed at reprogramming AML cells toward a differentiated cell state or to one that is responsive to alternative successful but limited AML therapies such as ATRA. Here, we propose that by combining bioinformatic analysis with inhibition of PPIns pathways, especially within the nucleus that we might discover new combination therapies aimed at reprogramming transcriptional output to control the cell state and attenuate uncontrolled AML cell growth. Furthermore, we outline how different part of a PPIns signalling unit might be targeted to control selective outputs that might engender more specific and therefore less toxic inhibitory outcomes.